2014
DOI: 10.4300/jgme-d-13-00355.1
|View full text |Cite
|
Sign up to set email alerts
|

The Residency Performance Index: An Effort at Residency Quality Assessment and Improvement in Family Medicine

Abstract: Background Residency programs are increasingly being asked to defend their quality, and that of the residents they produce. Yet “residency quality” is a construct that has not been well defined, with no accepted standards other than meeting accreditation standards. In 2009, the Association of Family Medicine Residency Directors developed a strategic plan that included the goal of raising the quality of family medicine training. Objective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…In fact, not all residency programs are accredited. Accreditation of a training program is needed in order to improve quality and facilitate exchange of trainees between institutions [5, 19]. …”
Section: Discussionmentioning
confidence: 99%
“…In fact, not all residency programs are accredited. Accreditation of a training program is needed in order to improve quality and facilitate exchange of trainees between institutions [5, 19]. …”
Section: Discussionmentioning
confidence: 99%
“…A convention of red, yellow, and green was chosen for the RPI, with green representing achievement of excellence in quality targets; yellow denoting adequate program quality for accreditation purposes but with room for improvement or caution; and red indicating metrics below accreditation standards, national norms, or targets promoted by family medicine professional organizations, based on published requirements or literature (Table 1). 13,14 Analysis of the aggregate data for the 6 years (2012-2017) that the survey was active revealed that 646 program-years of data from 248 unique FM residency programs could be reliably extracted. Adjusting for minor variations in the wording of survey questions over the years, the data can be grouped into categories of questions: (1) program accreditation and program leadership status, (2) family medicine center (FMC) resident clinical experience, (3) hospitalbased resident clinical experience, (4) procedural training, (5) residency program scholarship, and (6) graduate scope of practice.…”
Section: Methodsmentioning
confidence: 99%
“…11,12 We have previously described the process to develop this tool and its initial successes and challenges. 13,14 In 2018, the AFMRD Board made the decision to sunset the RPI due to insufficient return on investment as demonstrated by increasing software costs and staff time coupled with lack of growth in participation and only modest improvement in quality. This paper describes the lessons learned from an analysis of 6 years of data collected while the RPI was in use that can inform future quality and accreditation efforts implemented on a national level.…”
Section: Original Articlesmentioning
confidence: 99%
“…Finally, metrics for evaluation of success in training workers in Child Protective Services are lacking in that they typically address the training itself rather than competency and confidence. The residency program index (RPI) was implemented in 2012 to help programs identify strengths and areas for improvement in their educational activities and resident clinical experiences that could be tracked and reviewed as part of the annual program evaluation (Hoekzema et al 2014). This type of index could be developed for state child welfare agencies and maintained on a federal level for accountability.…”
Section: Disruption Through Trainingmentioning
confidence: 99%